Therapeutic options and drug delivery strategies for the prevention of intrauterine adhesions - Kou, Longfa; Jiang, Xue; Xiao, Shuyi; Zhao, Ying-Zheng; Yao, Qing; Chen, Ruijie (Journal of controlled release, 2020)
Intrauterine adhesions (IUAs) are bands of fibrous tissue that form in the endometrial cavity and associated with the increased risk of abnormal menstruation, recurrent pregnancy loss, secondary infertility, and pregnancy complications. Physical barriers, including intrauterine device and hydrogel, were clinical available to prevent the post-operational IUAs. But physically separation of the injured endometrium relies on the own limited healing power and often ends with recurrence. In recent years, the mechanisms driving IUAs treatment has validated the application of hormones, and further stem cell therapy has also led to the development of novel therapeutic agents with promising efficacy in pre-clinical and initial clinical studies. Still, it is challenging to delivery the therpaeutic factors to the injured uterus. Herein, in this review, we discuss the traditional intervention methods for the prevention of IUAs, as well as novel therapeutics and delivery strategies that will most likely change the treatment paradigms for better clinical outcomes. The combination strategy that using physical barriers as the delivery carriers for therapeutics might provide new alternatives for the prevention of IUAs. [Display omitted]